Green Public Procurement: Climate provisions in public tenders can help reduce German carbon emissions - Olga Chiappinelli; Friedemann Gruner; Gustav Weber (DIW Weekly Report, 2019)
This report estimates that government consumption and investment are responsible for at least 12 percent of German greenhouse gas emissions, mostly arising from the provision of public services and construction. Climate-friendly Green Public Procurement (GPP), which takes into account the carbon footprint of products and services in public tenders, can help reduce these emissions. Construction, and especially infrastructure, can be a main area for climate change mitigation through GPP. Yet the implementation of GPP practices in Germany is still limited and not focused on emission reduction. Based on a survey among procurement officials, this report shows that the main perceived barrier is the technical complexity of GPP combined with a low administrative capacity. Priority policy measures to overcome these barriers include triggering political commitment to GPP at the local level, enhancing specialized procurement capacities, and strengthening the provision of assistance to procurement authorities, for instance through competence centers on sustainable procurement.
Keywords: H57; Q56; Q58; 330; Green Public Procurement; government spending; carbon footprint accounting; climate policies